Poetry as Knowing - Folkart, Barbara (TTR)

(untitled) (Association canadienne de traductologie, 1999)
AbstractPoetry as Knowing — Like the pure sciences, poetry is first and foremost a cognitive instrument, one of the most rigorous modes of knowing that exist. Everything about it is shaped by the search for insight, or even truth. Poets are no more in the business of "making pretty" than molecular biologists or computer nerds; they put us into un-mediated contact with the grid of the world, force us to dig deeper than ever before into the amorphous business of being.This they do by "making it new". Poetry is a "counter idiomatic" practise, one that grates against the words of the tribe, its received ideas and its verities. And "form" — whether "free" or forged out of constraints — plays an all-important part in making it new for us. Form is decorative only to the illiterate. For the competent receiver, it is acutely, intensely functional.By giving it form, making it new, forcing us out of the lexicalized varieties that have gone stale on us, poetry makes us feel our way to new truths, or to a gut knowledge of old ones. Hence the maïeutic function of poetry.The very fact that poetry is so intolerant of the already-said is what explains the irreplicability or what Berman referred to as la lettre and makes the poem refractory to translation. Yet, most practitioners conceive of translation as a way of replicating what's already there. It's hard to imagine a more anti-poetic stance.